The Rāmāyaṇa of Vālmīki: An Epic of Ancient India, Volume V : Sundarakāṇḍa - Vālmīki (Princeton Library of Asian translations., 2016)
The fifth and most popular book of the Ramayana of Valmiki, the Sundarakanda, recounts the adventures of the monkey hero Hanuman in leaping across the ocean to the island citadel of Lanka. Once there, he scours the city for the abducted Princess Siti. The poet vividly describes the opulence of the court of the demon king, Ravana, the beauty of his harem, and the hideous deformity of Sita's wardresses. After witnessing Sita's stern rejection of Ravana's blandishments, Hanuman reveals himself to the princess and restores her hope of rescue. The great monkey then wreaks havoc on the royal park and fights a series of hair-raising battles with Ravana's generals. Permitting himself to be captured by the warrior Indrajit, Hanuman is led into the presence of Ravana, whom he admonishes for his lechery. His tail is set ablaze, but he escapes his bonds and leaping from rooftop to rooftop, sets fire to the city. Taking leave of Sita, Hanuman once more leaps the ocean to rejoin his monkey companions. This is the fifth volume translated from the critical edition of the Valmiki Ramayana. It contains an extensive introduction, exhaustive notes, and a comprehensive bibliography.